The role of colonic motility in low anterior resection syndrome - Varghese, Chris; Wells, Cameron I.; Bissett, Ian P.; O’Grady, Gregory; Keane, Celia (Frontiers in Oncology, 2022)
Low anterior resection syndrome (LARS) describes the symptoms and experiences of bowel dysfunction experienced by patients after rectal cancer surgery. LARS is a complex and multifactorial syndrome exacerbated by factors such as low anastomotic height, defunctioning of the colon and neorectum, and radiotherapy. There has recently been growing awareness and understanding regarding the role of colonic motility as a contributing mechanism for LARS. It is well established that rectosigmoid motility serves an important role in coordinating rectal filling and maintaining continence. Resection of the rectosigmoid may therefore contribute to LARS through altered distal colonic and neorectal motility. This review evaluates the role of colonic motility within the broader pathophysiology of LARS and outlines future directions of research needed to enable targeted therapy for specific LARS phenotypes.